1978
DOI: 10.1002/cne.901780203
|View full text |Cite
|
Sign up to set email alerts
|

Three bulbospinal pathways from the rostral medulla of the cat: An autoradiographic study of pain modulating systems

Abstract: Small amounts of 3H‐leucine were injected into discrete regions in the rostral medulla of the cat. Descending projections from these sites were studied with autoradiographic methods. On the basis of differential projections to the medulla and spinal cord, three distinct regions were delineated. Nucleus reticularis gigantocellularis (Rgc), located dorsally in the medullary reticular formation, projects primarily to “motor” related sites, including cranial motor nuclei VI, VII, XII, nucleus intercalatus, and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
1

Year Published

1981
1981
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 610 publications
(80 citation statements)
references
References 52 publications
4
75
1
Order By: Relevance
“…Reticulo-spinal neurons arising from additional areas of the medullary reticular formation were also described, using the retrograde axonal transport of horseradish peroxidase (HRP), in the cat (Kuypers and Maisky 1975), and in the opossum (Martin et al 1979), the autoradiography method in the cat (Basbaum et al 1978) and the combined retrograde HRP transport-immunocytochemical method in the rat (Ross et al 1981). Both medullary raphe nuclei and the medullary reticular formation project to every level of the spinel cord (Kuypers et al 1962;Nyberg-Hansen 1965;Martin et al 1978).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reticulo-spinal neurons arising from additional areas of the medullary reticular formation were also described, using the retrograde axonal transport of horseradish peroxidase (HRP), in the cat (Kuypers and Maisky 1975), and in the opossum (Martin et al 1979), the autoradiography method in the cat (Basbaum et al 1978) and the combined retrograde HRP transport-immunocytochemical method in the rat (Ross et al 1981). Both medullary raphe nuclei and the medullary reticular formation project to every level of the spinel cord (Kuypers et al 1962;Nyberg-Hansen 1965;Martin et al 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the reticulospinal fibers from the medulla descend in the lateral funiculus (Nyberg-Hansen 1965; Kuypers and Maisky 1977;Martin et al 1978;Tohyama et al 1979), including the dorsolateral funiculus (Basbaum et al 1978). Raphe-spinal fibers from the Rpa and Rm descend in the dorsolateral funiculus and from the Ro in the lateral portion of the anterior funiculus (Martin et al 1978) Reticulospinal and raphe-spinal fibers terminate on large parts of the spinal grey matter: in the lateral portion of the central grey matter around the somatomotor and visceromotor neurons, as well as in the dorsal horn (Dahlstrom and Fuxe 1964;Basbaum et al 1978;Martin et al 1979Martin et al , 1982Tohyama et al 1979).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomically, this circuit is in place. Both the RVM and adjacent areas receive direct afferent input from the superficial spinal dorsal horn and in turn send descending projections through spinal funiculi that terminate in the superficial dorsal horn, completing a spinobulbospinal loop (20)(21)(22)(23). We review below recent studies that document that spinal transection, or inactivation of supraspinal sites, prevents the expression of secondary hyperalgesia in a variety of animal models of persistent inflammatory, neurogenic, or neuropathic pain, thus providing the functional context in support of the anatomy (see Table 1).…”
mentioning
confidence: 99%
“…Ryall, unpublished observations) and are similar to those where others have shown that the microinjection of morphine causes behavioural analgesia (see Introduction). Furthermore, direct projections from some of these sites to the spinal cord have been reported (Basbaum, Clanton & Fields, 1978). Even if there were sites in the brainstem more sensitive to etorphine than those which we have studied the similarity of the ED50s in spinal and intact animals would suggest that such sites are unimportant for depression of dorsal horn responses when the opiate is given systemically.…”
Section: Discussionmentioning
confidence: 82%